Methodology In Preparing And Publishing Kitab 40 Hadis Membudayakan Sunnah - Wan Khairul Aiman, Wan Mokhtar (2014)
This research is focusing on methodology of preparing and publishing a book of 40 hadis Membudayakan As-Sunnah (MS) by Jabatan Agama Johor (JAJ) is being used widely in Johor. As instructed by JAJ, teaching and learning sessions with this book is a must especially in mosques and musolla. Meanwhile, MS’s quality through preparing and publishing is still not widely known. The question is what is the meaning by Membudayakan As-Sunnah (implementing As Sunnah)? How is the process of preparing and publishing MS? Can the quality of this book know as good in preparing and publishing? To answer these three questions need to solve two base questions. First, explain the meaning based of the name of MS. Second, identify the best methodology in preparing and publishing MS. This research is using qualitative method to analyze the content leads to the answer which is the MS’s name is suitable. Besides, the method done in producing MS is systematic and accurate. According to that, the publishing of MS is relevant due to its quality of publishing.